THE EFFECT OF THE PROBING PROMPTING LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF GRADE X STUDENTS IN HISTORY LEARNING AT SMK INFORMATICA CITY OF SERANG : Pengaruh Model Pembelajaran Probing Prompting terhadap Kemampuan Berpikir Kritis Siswa Kelas X Pada Pembelajaran Sejarah di SMK Informatika Kota Serang - Irma Wulandari; Arif Permana Putra; Agus Rustamana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the effect of the Probing–Prompting learning model on students’ critical thinking skills in history learning. A quantitative approach with a quasi-experimental design was employed. The population consisted of 188 tenth-grade students at a vocational high school in Indonesia. Using purposive sampling, two classes were selected as research samples: one experimental class applying the Probing–Prompting model and one control class applying the Discovery Learning model. Students’ critical thinking skills were measured using a multiple-choice test based on Ennis’s critical thinking indicators. Data were analyzed using descriptive statistics and independent sample t-tests. The results indicate that the experimental class achieved a higher mean post-test score (69,38) compared to the control class (51,36). The t-test results show a significance value of 0,000 (< 0,05), indicating a statistically significant difference between the two groups. These findings demonstrate that the Probing–Prompting learning model has a significant positive effect on students’ critical thinking skills in history learning. This study contributes to the development of student-centered instructional strategies that promote higher-order thinking skills in history education.